Face recognition with accessories using Eigenfaces - Toh, Safarudin Wilyam (Nanyang Technological University, 2024)
This study uses a dataset of unoccluded faces for training to examine the effectiveness of using an eigenface approach to identify faces covered by accessories, particularly sunglasses. The robustness of the eigenface method against partial face occlusion is assessed using principal component analysis, a method often employed in the field of computer vision to perform successful human face detection.